2004
DOI: 10.1023/b:toca.0000029731.51530.f7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Support in Lean DeNOxCatalysis

Abstract: FTIR and pulse thermal analysis were applied to investigate catalysts containing Pt (1 wt%)/Ba (17 wt%) supported on c-Al 2 O 3 , SiO 2 and ZrO 2 . The aim was to learn how the support material affects the thermal stability of barium carbonate and its activity in the reaction to bulk Ba(NO 3 ) 2 . The lower thermal stability of BaCO 3 in alumina supported samples was found to influence the formation of barium nitrate during the NO x storage process. Quantification of Ba(NO 3 ) 2 formed during NO x storage indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…4, NO x evolution was not detected below 300°C. This is in line with literature reports that thermal desorption of NO x does not occur below the temperature at which adsorption was performed [12][13][14]. Decomposition of the adsorbed NO x species commenced slightly above 300°C, as evidenced by the evolution of NO x , this process extending up to 500°C for both catalysts.…”
Section: Thermal Stability Of Stored No Xsupporting
confidence: 88%
“…4, NO x evolution was not detected below 300°C. This is in line with literature reports that thermal desorption of NO x does not occur below the temperature at which adsorption was performed [12][13][14]. Decomposition of the adsorbed NO x species commenced slightly above 300°C, as evidenced by the evolution of NO x , this process extending up to 500°C for both catalysts.…”
Section: Thermal Stability Of Stored No Xsupporting
confidence: 88%
“…A similar cooperative effect was also found on the decarbonated BaCO 3 surface [9] -adsorption of a NO 2 pair causing desorption of one CO 2 molecule with an energy gain of 1.5 eV and complete decarbonation of the BaCO 3 surface (adsorption of two NO 2 pairs and desorption of two CO 2 molecules) resulted in an energy gain of 2.2 eV. Although most experimental studies focused on BaO supported on various oxide substrates and demonstrated that the nature of the support materials has strong influence on the sorption property of BaO toward NO x [10,11], previous theoretical studies utilizing either periodic supercells or molecular clusters of BaO were almost exclusively focused on the bulk BaO surface or unsupported BaO clusters [12][13][14][15]. In the present letter, we report our results of the density functional theory (DFT) study on the substrate effect of c-Al 2 O 3 on BaO clusters towards NO 2 adsorption.…”
mentioning
confidence: 97%
“…Assuming that NO x species are stored as nitrates allowed to quantify the amount of NO stored by TPRD of NO x saturated catalysts and to derive the fraction of active Ba [9,24,26]. The NO x storage efficiency is presented in figure 4 in terms of fraction of Ba involved in the NO x storage process versus the total Ba loaded.…”
Section: Influence Of Ba-loading On Thermal Stability and No X Storagmentioning
confidence: 99%
“…Al 2 O 3, CeO 2 , ZrO 2 , Ce-Zr-oxides and SiO 2 are widely used in the control of combustion pollutants [13][14][15][16][17][18][19][20][21] and in our studies we specifically addressed the comparison of these oxides as supports in Pt-Ba based NO x storage-reduction catalysts. Preliminary results on Pt-Ba catalysts supported on different oxides indicated different NO x storage behavior depending on the support [9].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation